Menjadikan Indonesia Negara Ekspor Utama Dunia - Muhammad Chairuladnan Syaifullah Islami; Nur Cahyo Wibowo (CV ODIS, 2023)
Indonesia is a country located in the Southeast Asia region and flanked by the two continents of Asia and Australia, Indonesia is one of the countries with the largest islands and population. From the questionnaire distributed to respondents, data was obtained to make Indonesia a world exporter, the data was processed using descriptive analysis methods to produce the answer that Indonesia has the potential to become the world's leading exporter, this is divided into several factors as why Indonesia can become the world's leading exporter. In terms of Indonesian waters, it has several potentials, Indonesia is known as a maritime country because it is dominated by the ocean, in the fisheries sector it is superior because Indonesia's marine products are of excellent quality besides being abundant so they can meet the demand of countries that need a large supply of marine animals.